Menjamin Kebebasan Individu Pasca Pandemi: Framework Trust Government Untuk Membangun Kepercayaan Publik - Aulia Izzah Azmi; Putra Satria (Sociology Department, Brawijaya University, 2022)
After the COVID-19 pandemic, the government experienced a new challenge, namely restoring public trust in the government due to the reduction of individual freedom of the community on the basis of emergency crisis conditions. This study focuses on explaining (1) the dynamics of public trust in the government in the post-pandemic phase (2) the tendency of the government to take strategic steps on a top-down basis so that it threatens individual freedoms affected by applicable policies and regulations (3) frameworks that can be applied to build public trust so that collaboration between sectors in dealing with the after effects of the pandemic can be achieved. The research method used in this article is a Systematic Literature Review by collecting primary data sourced from accredited journal articles and media news sources. The results of this study reveal that individual freedom in an emergency is limited and this has an impact on the crisis of Indonesian people's confidence in the government and has logical consequences for public stability in responding to policies. At the end of the discussion, the researcher offers a framework to build public trust after the COVID-19 pandemic that is oriented towards citizen engagement. Keywords: civil liberty, citizen engagement, post pandemic, public trust